Notas sobre la teoría de la validez de la norma canónica: existencia, validez formal, validez material, vigencia, eficacia y efectividad (Stato, Chiese e pluralismo confessionale, 2023)
Notes on the theory of the validity of the canonical norm: existence, formal validity, substantive validity, efficacy and effectivenessSOMMARIO: 1. Planteamiento: proseguir la intuición inicial de la Escuela laica italiana y corregir la actual ‘canonizatio práctica’ - 2. La rationabilitas como elemento central de la teoría de la norma canónica - 3. Conveniencia de la teoría de la norma canónica - 4. Notas sobre la teoría de la validez de la norma canónica - 5. Existencia / Inexistencia - 6.I. Validez formal / Invalidez formal; Validez material / Invalidez material - 6.II. Origen y necesidad de la distinción - 6.III. Dos tipos de normas humanas: principios y reglas - 6.IV. El principio de jerarquía normativa: formal, material y estructural - 7. Vigencia / Falta de vigencia - 8. Eficacia / Ineficacia - 9. Efectividad / Inefectividad - 10. Conclusión.ABSTRACT: Canonical science, since its birth, has contributed to the progress of canon law when it has maintained a dialogue with the juridical theory and dogmatic of each epoch. In this direction, the Italian secular school gave canonical science a decisive impulse, later paralyzed as a result of some theories such as the canonizatio of Vincenzo del Giudice. The dialogue between canon law and juridical science is necessary to extract the progress made by the 1983 Code with the formalization of fundamental rights. With some excesses corrected thanks to the proposals of Lombardia and Hervada, the original intuition of the Italian secular school was correct and it is convenient to accompany and clarify the growing protagonism of the legislative activity of the Church. From this perspective favorable to dialogue with juridical science, revalued by the call to interdisciplinarity of the Apostolic Constitution Veritatis Gaudium, the article continues the reflection on the canonical norm raised with various nuances by the doctrine, and offers some notes on the theory of the validity of the canonical norm.